EFEKTIFITAS PENDIDIKAN KESEHATAN TERHADAP PENINGKATAN PENGETAHUAN REMAJA PUTRI MENGENAI PENANGANAN DISMENORE DENGAN ABDOMINAL STRETCHING DI SMP NEGERI 1 CISALAK KABUPATEN SUBANG TAHUN 2020 - Hilya Auliya RM; Nurhidayah; Dina Martha Fitri; Diah Warastuti (STIKES MITRA RIA HUSADA, 2022)
Effectiveness of Health Education Towards The Increase of Young Women On The Treatment Of Dismenorrhea With Abdominal Stretching In SMP Negeri 1 Cisalak Subang 2020ABSTRACTHealth education is a series of experiences that influence an individual's knowledge. The success of health counseling depends on the component or the media of learning. Based on the results of the recapitulation data of SMP Negeri 1 Cisalak’s female students who had to leave their study activities and rest at home due dismenorrhea to 33%, the figure is quite high compared to the incidence of other diseases that cause students to rest at home. The purpose of this research is to know the effectiveness of health education through video and leaflets on young women's knowledge of the treatment of dismenorrhea with abdominal stretching in SMP Negeri 1 Cisalak. This research uses Quasi Experiment Design and Non Equivalent Control Group (pretest posttest control group design) approach method. The sample of this research is 153 students who were taken from the 3rd grade students of SMP Negeri 1 Cisalak. Respondents will be divided into two groups. A total of 77 were included in the video group and a total of 76 were included in the leaflet group. The instrument used is a questionnaire. The study was conducted in August 2020. The results used Paired samples T-Test with an average knowledge score of 80.07 leaflet group and 83.70 video group with P-Value of 0.000. The conclusion of this study is that there were significant differences in average scores between leaflet and video groups. So health education is more effectively provided with video media. It is hoped that this research adds insight into health education through video media.Keywords: Dismenorrhea, Abdominal Stretching, Knowledge, Health Education, Video Media, Leaflet Media